Inhibition of ADP-Induced Platelet Aggregation by Adenosine Tetraphosphate - Harrison, Margaret J.; Brossmer, R (Thrombosis and Haemostasis, 1976)
In contrast to previous reports, highly purified adenosine tetraphosphate (AP4) does not induce the aggregation of platelets but inhibits the aggregation and release reaction in platelet-rich plasma promoted by ADP. The inhibitory action of AP4 on the aggregation by ADP is compared with that of AMP and ATP. The data presented suggest a competitive manner of inhibition of the ADP-induced aggregation by AP4.